P4 3 Piezoelectric Power Generation for Street Lights - Owusu Boamah, Jeremy; Fotedar, Ayush; McCrea, Alec (Physics Special Topics, 2024)
This study examines the potential of harnessing vehicle traffic in Leicestershire to power street lighting using the direct piezoelectric effect. Our model generated approximately 4.8 × 102 J of energy, which falls significantly short of the estimated energy requirement of 3.3 × 1013 J to meet the full demands of street lighting.